Radioactivity of Ferro-Manganese Formations in Seas and Lakes of the U.S.S.R. - Kurbatov, L M (PANGAEA, 1935)
The radioactivity of bottom sediments has been but little investigated. Data published by Joly, Pettersson, Piggot and Iimori refer to determinations of radium, contained mainly in oceanic deep-water sediments in red clays, radiolarian, globigerina oozes, blue muds and manganese concretions. The determinations have shown the manganese concretions to be richest as regards content of radium (up to 10-8 per cent); red clays and radiolarian ooze also possess a rather high content of radium. Other types of sediments are less rich in radium.
Annotated record and radium content of the detailed examination of manganese nodules from lakes in Karelia, Russia
Keywords: Deposit type; DEPTH, sediment/rock; Description; Identification; Lake_Konch_K; Lake_Onega_K; Lake Konch, Karelia,Russia; Lake Onega, Karelia, Russia; NOAA and MMS Marine Minerals Geochemical Database; NOAA-MMS; Position; Quantity of deposit; Radium; Size; Visual description